Intercultural language learning in a sister school partnership between Indonesia and Australia - Iryanti, Heni Dwi; Madya, Suwarsih (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2018)
This case study aimed to: (1) reveal how intercultural language learning occurred within a sister school partnership in an Indonesian public high school in Yogyakarta, and (2) describe student behaviours perceived to be indicative of intercultural language learning. Using an ethnographic approach through observations and dialogues, this study investigated real life interactions occurring among the research participants within the uniqueness of the partnership between an Indonesian public high school in Yogyakarta and its Australian school partner. The results showed that intercultural language learning occurred in the forms of learning experiences which engaged the students in interaction, observation and reflection with the target community. A number of indicators of intercultural language learning were revealed in the students behaviours within four authentic language experiences including exploring language and culture, noticing verbal and non-verbal cultural behaviours, making connections between home and the target language and culture, and reflecting on the development of a third or intermediate personal position between cultures.